Classical Music Interventions to Reduce Anxiety in Pregnancy - Permatasari, Ineke; Farona, Isabela (Jurnal Ilmiah Kesehatan Rustida, 2025)
To calming mind, people can be intend with music therapy and free their body from mentally, physicaly, and emotional stress who rapidly experience by pregnant women, its also a train to patients to be able relax. Pregnant women generally experience anxiety due to changes in body shape, hormones or preparation for childbirth. This experience study conducting and providing classical music as therapy a interventions to pregnant women which proven in several study to reducting anxiety. Use a quasi-experimental design, one group pre and post test research design. This aimed a purposive sampling tehniques of 30 respondents. Study performed a significant relationship among classical music that decreasing a level of anxiety of pregnant women showed a p value = 0.000 < 0.05, N 30. Conclusions that there is a significant effect between classical music as therapy to reducing a level of anxiety of pregnant women.